Production and litter decomposition rate in secondary vegetation of Tabasco, Mexico - García-Domínguez, Antonio; Cámara Cabrales, Luisa del Carmen; van der Wal, Johannes Cornelius; Martínez Sánchez, José Luis (Instituto de Ecología, A.C., 2020)
The dynamic between litter fall and its decay is part of the functioning of ecosystems. The production, loss and rate of decomposition of forest litter and secondary vegetation in ecogeographic units (EU) of mountain slopes, terraces and fluvial plains in the subregion of the rivers of Tabasco in Mexico were evaluated. In each EU, six conglomerates were established with four plots of 10 m x 40 m and in three plots of each conglomerate, 6 traps of 1 m2 were distributed (n = 144), which were collected from March 2014 to March 2015. To determine the remaining weight and the decomposition rate, the decomposition bags method was used, initially with 10 g of litter per bag (n = 384). The period to determine the decomposition was comprised from June 2014 to March 2015 and monthly, four bags were collected per conglomerate, which were dried at constant weight. The results show that the litter production of the secondary vegetation in the EU is similar to that of primary vegetation in two zones, while in only one of them it was higher. The weight loss and decomposition rate showed that, for primary vegetation, both are slightly higher than for the acahuales. These results may be significant due to the inexistent works about the production and decay of litter in the ecogeographic unit, that may help to secure the management and conservation of secondary vegetation in Tabasco state.